ON SUSTAINABILITY AND URBAN CONTEXT PRESERVATION: TWO DIPLOMA THESIS AT UAUIM BUCHAREST - CALIN, Alexandru (Journal of Building Energy & Environment, 2019)
The article has as a starting point a quote from a recent lecture that Rem Koolhas, the world renowned architect and theoretician, has given to Harvard students and which is about sustainability and the real and substantial concerns on this extremely current topic. The subject is not new but it became a hot topic in recent years in both architecture critics and practice. It is also one of the important topics that concern us within the University Department and a constant addition to the research topics proposed by our students for their final diploma projects. As a tutor, together with my colleague PHD.Prof.Melania Dulamea, we seek along with our students the most profound approach to the problems of the modern city and try to provide viable answers and alternatives in their research projects. The contemporary city and its development represent one of our major concerns.The current article is based on two diploma projects presented in this summer final jury at UAUIM Bucharest.Both projects propose different directions of investigation and adequate answers to the problems of the contemporary city and the way in which it can be developed sustainable and efficiently: In the first case, Catalin Serbu discusses the conversion of a currently decommissioned historical building in a central area of Bucharest and how this building can be rendered to the local community in a gesture meant to repair and generate new urban activities. In the second, Iulia Moraru explores the potential of an pos-industrial city, Ploiesti, and the ways in which research and new technologies can become engines for development and are in the same time capable to ensure a re-branding process for the post-industrial city.